Web of Things (IoT): Shrewd Living and Way of life - Patel, Vedanti; Vegad, Mansi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In our everyday life we can see that innovation is advancing continually. The web of things (IoT) contains different applications and advancements that are accessible in brilliant homes, shrewd water system, and medical services. The IoT goes about as an extended variant of the web, which furnishes us with the information we really want to productively carry on with our lives more. It depends on interfacing up gadgets utilized every day. The fundamental goal of this paper is to figure out how to involve IoT in Brilliant Homes, Medical services, and Farming.